Comparison of rCCD and BBD design for reactive separation of gallic acid using trioctylamine in lauryl alcohol (Indian Journal of Chemical Technology (IJCT), 2025)
Rotatable Central Composite Designs (rCCD) and Box–Behnken Design (BBD) have been used as statistical multivariate methods in the optimization of reactive separation of gallic acid from the aqueous solutions using trioctylamine as extractant dissolved in lauryl alcohol. Effects of variable such as initial concentration of gallic acid (0.02- 0.04 kmol.m-3), extractant (20–40%, v/v in diluent), temperature (298-318 K) on the separation efficiency of gallic acid have been investigated. rCCD model predicted the maximum separation efficiency of 84.54% at the conditions of initial acid concentration (0.031 kmol.m-3), extractant volume percentage (17.20 % v/v in diluent ) and temperature (298 K) as the optimal solution. BBD model suggested that the optimum conditions are initial acid concentration (0.031 kmol.m-3), extractant volume percentage (17.82 %v/v in diluent) and temperature (298.68 K) provided separation efficiency of 83.71%. The exactness of the two models is judged based on the actual experiments at some random points. Results indicate that the rCCD and BBD are both are reasonably accurate with rCCD slightly more accurate as shown by lower residual square error obtained using the values predicted by both the models.